Performance Appraisal and Its Impact on Staff Morale: An Exploratory Study of Selected Companies in Nairobi, Kenya - Maonga, Oliver Washington (2010)
Many organizations are faced with problems such as dissatisfaction of employees, lack of motivation to perform high labour, absenteeism among others, which result to poor employee performance. This study aims at finding out whether performance appraisal has an impact on staff morale. In the research the author was guided by the following aspects/objects. - To investigate how performance appraisal is being carried out in organizations. - To discover the relationship between performance appraisal and employees‟ morale. - To find out whether employer and employee have the same understanding of the intention of performance appraisal. - To explore challenges faced by organization in improving employees‟ morale via performance appraisal. The study was carried out at Firestone East Africa Ltd, American Life Insurance Company (Alico Kenya) Ltd, and Kenya Medical Supplies Agency (K.E.M.S.A). Central Glassworks Limited, Ministry of Transport and Communication. The instruments that were used by the author for data collection were interview and observation, questionnaire and case study. The data collected was analysed and presented in bar graphs and pie charts. The author concludes that when performance appraisal is properly conducted employees are motivated and at the end of the day the organization achieves the goals and objectives of its being.